2000
DOI: 10.1007/s004310050061
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory distress in a neonate with an enlarged thymus

Abstract: Thymic enlargement is unusually associated with neonatal respiratory distress but should be considered in the differential diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Thymus hyperplasia is defined as an enlarged thymus consisting of normal thymic tissue, it is generally asymptomatic. Some authors have reported cases of enlarged thymus leading to respiratory symptoms (dyspnea, cough, stridor or wheezing) (1,2), early in infancy. Normal evolution is involution with disappearance of respiratory symptom before the third year of life.…”
mentioning
confidence: 99%
“…Thymus hyperplasia is defined as an enlarged thymus consisting of normal thymic tissue, it is generally asymptomatic. Some authors have reported cases of enlarged thymus leading to respiratory symptoms (dyspnea, cough, stridor or wheezing) (1,2), early in infancy. Normal evolution is involution with disappearance of respiratory symptom before the third year of life.…”
mentioning
confidence: 99%